”BETA DISINI” Pelatihan Dukungan Psikologi Awal untuk Pencegahan Bunuh Diri bagi Mahasiswa di Kota Kupang: Indonesia - Manafe, Rizky Pradita; Benu, Juliana Marlin Y; Wijaya, R. Pasifikus Christa (Jurnal Abdimas Madani dan Lestari (JAMALI), 2025)
The number of suicides increases every year. In 2023, 11 students will be recorded and published in mass media and social media. This service aims to enable students to understand the symptoms of people with suicidal tendencies (OKBD) and carry out prevention through early psychological support. The methods used in this service are lecturing, group discussions, games and role play. The training participants are student representatives from universities in Kupang City. The number of participants was 22 participants. The results of the service show that there is an increase in the average score before and after the service. Before the service the average value of participants' knowledge was 37.9, while the average value of participants' knowledge after attention was 54.4. This service has not optimally changed the participants' skills, because time is limited.